THE INDUCING COMPOUND OF FUSARIC ACID FOR RESISTANCE OF FUSARIUM WILT DISEASE IN FAMILY ORCHIDACEAE - Elsi Diana; Endang Nurcahyani (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2022)
Orchids are plants that belong to the Orchidaceae family. Orchid have charming flowers because they have various colors, shapes and sizes, and bloom perfectly and are long-lasting. In the process of growth, orchids can be attacked by several diseases, one of which is fusarium wilt caused by the fungus Fusarium oxysporum. Fusarium oxysporum produces a non-specific mycotoxin compound, namely fusaric acid. Fusaric acid at non-toxic concentrations can help induce the synthesis of phytoalexins, which is a form of plant response to inhibit pathogen activity. Based on the results of reviews from several journals, it can be concluded that fusaric acid compounds can be used as resistance compounds to fusarium wilt disease in orchids.